ANALISA PENGARUH KECEPATAN MOTOR INDUKSI TERHADAP KINERJA PUTARAN MESIN PENCACAH SAMPAH PLASTIK MENGGUNAKAN TIMER H3BA - Wiji Lestariningsih (Universitas Muhammadiyah Metro, 2026)
This study aims to evaluate the impact of variations in induction motor speed on the performance of PET (Polyethylene Terephthalate), PP (Polypropylene), and LDPE (Low-Density Polyethylene) plastic waste shredding machines. The developed machine is designed to cut plastic waste into small pieces. As a driver, a single-phase AC electric motor with a maximum speed of 3000 Rpm is used. The trial was conducted with three variations in motor speed: 2000 Rpm, 2500 Rpm, and 3000 Rpm, to measure the daily production capacity of the machine in shredding plastic waste. The results showed that motor speed had a significant effect on the production capacity of the machine. Of the three types of plastic tested, namely PET, PP, and LDPE, the PET type produced the highest production capacity. At a speed of 2000 Rpm, the production capacity reached 58 kg/day; at 2500 Rpm, it increased to 64 kg/day; and at 3000 Rpm, the production capacity reached 77 kg/day. This study aims to develop an efficient plastic waste shredding machine technology by utilizing the H3BA timer. The integration of this timer is expected to improve the control of the machine's operational time, so that the plastic shredding process becomes more regular and energy efficient. This machine not only increases efficiency in plastic waste processing, but also supports environmentally friendly recycling efforts.